Ekstrak Air Jahe (Zingiber officinale Roscoe) Menghambat Akumulasi Kolesterol pada Makrofag - Aisyah Tri Septiana (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2004)
Water extract of ginger rhizomes has been reported to protect low density lipoprotein (LDL) oxidation. We investigated the effect of these extract enrichment on the prevention of cholesterol accumuation in macrophage. Water extract of ginger rhizomes was suplemented on LDL isolate (2150 idg/m1 LDL), oxidized with CuSO4 and incubated on macrophage culture. These extract also was suplemented on macrophage culture before incubated with LDL and FeCl2. The corresponding esterified cholesterol accumulation was analized from macrophage culture. Result showed that water extract of ginger rhizomes suplementation on LDL isolated before CuSO4 oxidation and on medium macrophage culture before incubation with LDL and FeCl2 reduced 69,07 % and 43,21 % of esterified cholesterol accumulation from macrophage, respectively. This research has shown that water extract of ginger rhizomes is capable of prevention cholesterol accumulation in macrophage.